Chapter Effects of an experimental online education support on lectures fruition and teaching effectiveness - Martini, Maria Cristiana (Proceedings e report, 2021)
In this paper, we describe and discuss the implementation, the effects, and the consequences of an experimental service designed to capture, record, edit and stream video lectures. This service, named ONELab, is operating since September 2017 at the Department of Communication and Economics of the University of Modena and Reggio Emilia to support the courses offered by the six degree programs available at the Department. Before the pandemic emergency, traditional face-to-face classes were regularly held, but ONELab was intended to provide flexibility to the educational contents (i.e., no time and geographical constraints) and to improve the students' learning process. The usage analyses show that, when given the opportunity, students tend to customise the learning process to their needs and life-style, with a large quote of usage in the late afternoon/night hours and during the week-ends. Video lectures are watched mostly during the teaching semester, but a significant part of students resort to watch them when the semester is over. The number, frequency and variety of accesses allow to describe different styles of usage, and students who use ONELab show better achievements, both in terms of acquired credits and in terms of grades, than those who never accessed the system. Moreover, some usage styles can help predicting the risk of dropout, signaling students who should be furtherly supported in order to prevent them from abandoning their studies.